The Critical Role of Tax Literacy Among Generation Z in Supporting the Indonesia Emas 2045 Vision - Aswat, Ibnu (CV. Green Publisher Indonesia, 2025)
Indonesia aims to become a developed country by 2045 through the vision of Indonesia Emas (Golden Indonesia), which emphasizes the critical role of youth, particularly Generation Z, in supporting national development. One essential component of sustainable development is tax revenue. However, the low level of tax literacy among the younger generation may hinder the optimization of state revenue. As Generation Z is a digitally native demographic with strategic potential, enhancing their understanding of taxation is crucial to ensure the fiscal sustainability of the nation. To evaluate the level of tax literacy among Generation Z in Indonesia and examine its contribution to the achievement of the Indonesia Emas 2045 vision. This research adopts a qualitative phenomenological approach. Data were collected through in-depth interviews, field observations, and focus group discussions (FGDs) involving high school students and university students in Pontianak City. The findings indicate that although Generation Z has broad access to digital technology, their level of tax literacy remains relatively low. A lack of understanding about the function of taxes, as well as tax rights and obligations, emerged as key issues. However, the research shows that effective tax literacy can significantly improve tax awareness and compliance, which are essential for supporting sustainable development. This research highlights the strategic role of tax literacy in national development and emphasizes the need for tax education approaches that align with the digital and social characteristics of Generation Z. It also offers policy recommendations based on a localized context (Pontianak City), providing actionable insights for national policymakers.